Comparative Essay on Returns to Education in Palestine and Turkey - Aysit Tansel; Yousef Daoud (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
This study exposes a comparative treatment of the private returns to education in Palestine and Turkey over the period 2004-2008. Comparable data, similar definitions and same methodology are used in the estimations. The estimates are provided first for average returns to education second for returns at different levels of schooling and finally for returns by different sectors of employment. The results suggest that returns to schooling are higher for Turkey at the various levels of education for females and males and for both years 2004 and 2008. It is believed that the relative size of the Palestinian economy and the uniqueness of subjugation to military occupation contribute greatly to this result. In 2008, returns are lower than 2004 levels for all levels of education; the pattern is less obvious for Turkey across the various levels. However, the 2008 crisis seems to have influenced the more educated more severely (MA and above) in both countries. Female returns to education are higher for women than men in both countries; the gender gap has worsened in 2008, but more so for Palestine. The median ratio of male to female return is 0.55 (university) in 2004 and decreased to 0.17 (high school) in 2008 in Palestine. The corresponding figures for Turkey are 0.79 and .082 (both for high school). Finally, it was found that the selectivity corrected return estimates are lower than the OLS estimates in Palestine while they are higher than the OLS estimates in Turkey.
Keywords: J16; J24; J31; J45; O31; 330; Returns to Education; Mincer Equation; Gender; Palestine; Turkey; Weiterbildung; Allgemeinbildung; Bildungsertrag; Geschlecht; Palästina; Türkei